A Comparison of Eucheuma cottonii Seaweed Cultivation in Monoculture and Polyculture Systems - Nainggolan, Putri Febrine; Arthana, I Wayan; Dewi, Ayu Putu Wiweka Krisna (Advances in Tropical Biodiversity and Environmental Sciences; Vol 6 No 1 (2022): ATBESDO - 10.24843/ATBES.2022.v06.i01.p04, 2022)
Seaweed is a commodity that has high economic value and benefits. The implementation of seaweed cultivation is quite short and the export market opportunities are wide open because the need for seaweed is quite large. This study aims to determine the growth rate of seaweed with monoculture and polyculture cultivation systems and the survival rate of abalone in polyculture cultivation. The research used an experimental method with Completely Randomized Design (CRD) consisting of two treatments and three replications. The cultivation system in this study was seaweed monoculture Eucheuma cottonii with an initial weight of 100 gr and 100gr seaweed polyculture with abalone Haliotis squamata, each polyculture culture net bag containing 50 abalones. The value of the specific growth rate of monoculture seaweed was 2.21%/day, lower than the specific growth rate of polyculture, which was 3.61%/day. T-test analysis showed the value of sig = 0.049 < = 0.05, which means that there is a significant difference between the treatment of monoculture cultivation and polyculture cultivation. The abalone growth rate value ranged from 0.78-0.91%/day and the abalone survival rate ranged from 68-76%. Changes in environmental conditions affect the condition of abalone and seaweed so that the survival value of abalone is quite low and seaweed is infected with an ice-ice disease which causes a decrease in seaweed weight gain in the final week of the study period.